SEMIOTICS ANALYSIS TOWARD INDONESIAN HALAL LOGO - Mohd. Norma Sampoerno; Maratun Saadah; Sean Popo Hardi (Universitas Mathla’ul Anwar Banten, 2022)
This study aims to provide a semiotic analysis of the Indonesian halal logo issued by the Halal Product Assurance Agency (BPJPH) of the Republic of Indonesia. The elements in the logo are considered to have messages per an institution's vision, mission, soul, and personality as well as Halal Logo. his study uses a semiotic analysis method to determine the meaning of the halal logo. This research study found that the Indonesian halal logo represents the shape of Gunungan and the Surjan or Lurik Gunungan motif on wayang kulit in the shape of a pyramid, pointing upwards. The shape of the Gunungan and the Surjan or Lurik Gunungan motif form Arabic calligraphy consisting of the letters Ha, Lam Alif, and Lam in a series to form the word Halal, and the Surjan motif, which is also called piety clothing, contains deep philosophical meanings.